2001
DOI: 10.1023/a:1011019417236
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Dietary flavonoid-mediated induction of intestinal UGT1A1 may be important for the glucuronidation and detoxification of colon and other carcinogens as well as for the presystemic metabolism of therapeutic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The flavone chrysin increased mRNA-levels, protein expression and enzyme activity of the UGT isoform UGT1A1 in intestinal Caco-2 and hepatic Hep G2 cells after an incubation time of several days [213][214][215]. Other flavones like acacetin, apigenin, baicalein, diosmetin and luteolin as well as the flavonols quercetin and kaempferol increased either activity or transcriptional activation of UGT1A1 in Hep G2 cells [199,200].…”
Section: Interaction Of Flavonoids With Phase II Conjugation Enzymesmentioning
confidence: 99%
“…The flavone chrysin increased mRNA-levels, protein expression and enzyme activity of the UGT isoform UGT1A1 in intestinal Caco-2 and hepatic Hep G2 cells after an incubation time of several days [213][214][215]. Other flavones like acacetin, apigenin, baicalein, diosmetin and luteolin as well as the flavonols quercetin and kaempferol increased either activity or transcriptional activation of UGT1A1 in Hep G2 cells [199,200].…”
Section: Interaction Of Flavonoids With Phase II Conjugation Enzymesmentioning
confidence: 99%
“…Studies have shown that human mammary cells have the capacity to metabolize the parent compound PhIP as well as the hydroxylated intermediates [50][51][52]. PhIP is glucuronidated by UGT1A1 in the human colon carcinoma cell line Caco2 [53] and human prostate cells have also been shown to metabolize PhIP ( [54,55], Kulp, personal observations). The metabolic pathways and the metabolites produced during PhIP bioactivation in these target organs have not been fully determined.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that SN50 (a NF-kB translocation inhibitor) could enhance the induction of UGT1A1 by apigenin, it was believed that UGT1A1 induction by apigenin might be associated with NF-kB translocation 85 . In addition to apigenin, quercetin was also shown to markedly increase the glucuronidation activity in Caco-2 cells 80 . The significant increase in glucuronidation activity might result from increasing expression levels of UGT1A6 (at 50 μM of quercetin) and UGT1A1 86,87 .…”
Section: Effects Of Flavonoids On Phase II Enzymesmentioning
confidence: 97%
“…It suggested that flavonoids could play an important role in modulation of sex hormones in humans and provide us with a possible means to prevent and manage prostate cancers. In addition, chrysin was reported to be able to induce UGT1A1 specifically, both in Caco-2 and HepG2 cells 78,79,80 . However, UGT1A6, UGT1A9 and UGT2B7 were not affected by the chrysin treatment 80 .…”
Section: Effects Of Flavonoids On Phase II Enzymesmentioning
confidence: 99%
See 1 more Smart Citation